Reassessing the Variables Used to Measure Public Perceptions of Scientists. Issue 1 (February 2021) - Besley, John C.; Lee, Nicole M.; Pressgrove, Geah
Both academics and science communication practitioners have long been interested in the public's perceptions of scientists, impacts of those perceptions, and how communication tactics can affect them. Despite this interest, perceptual variables (e.g., trustworthiness, credibility, and fairness) are inconsistently conceptualized and operationalized within the literature. Through an examination of existing scales and a national survey ( N = 605), this study suggests that communication researchers and practitioners should consider focusing on four distinct dimensions of trust. We label these competence, integrity, benevolence, and openness.